Euro Area Policies : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
The paper discusses the purpose, properties, and theoretical foundations of various indicators of inflation and also describes the forecasting methodology and performance of these indicators. It reviews the successful European labor market reform experiences and analyzes regulatory and supervisory frameworks in the European Union (EU), and assessments carried out under the IMF-World Bank Financial Sector Assessment Program (FSAP). It also investigates whether the cross-country correlation of bank business in Europe makes a good case for pan-European supervision.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet